THE EFFECT OF PEER INTERACTION ON SELF-CONFIDENCE OF GRADE XI STUDENTS OF SMAN 6 CITY OF BOGOR - Firdaus, Nazla Hana; Rosidah, Noneng Siti; Taqwa, Hafiz (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
Adolescence is a crucial period in individual development, where individuals not only form their self-identity but also strengthen their self-confidence, which will serve as the foundation for navigating adult life. Self-confidence, as the belief in one's own abilities, plays a vital role in facing life's challenges. However, many adolescents find it difficult to develop self-confidence. Various external and internal factors can influence the development of self-confidence, one of which is peer interaction. Peers play a significant role in adolescents' social processes, not just as companions in daily activities but as sources of social and emotional support. Positive peer interactions generally lead to higher self-confidence, while negative or pressuring interactions can result in a decrease in self-confidence. This research aims to explore the impact of peer interaction on the self-confidence of 11th-grade students at SMAN 6 Kota Bogor. Using a quantitative approach with descriptive correlational design and simple linear regression analysis, the study reveals that positive peer interactions significantly influence the students' self-confidence. The findings are expected to contribute to the development of counseling and guidance strategies that can help foster healthier social relationships and, ultimately, improve students' self-confidence. This research is particularly relevant in the Indonesian context, where peer interactions in schools are deeply influenced by cultural and social dynamics